Teori Budaya dalam Organisasi Landasan Nilai untuk Efektivitas dan Keberlanjutan Lembaga - Suheri; Susanto; Siti 'Aisyatunnadiya (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2026)
This study aims to examine the theory of organizational culture and its implementation in the context of Islamic educational institutions. Organizational culture is understood as a system of values, norms, symbols, and practices that shape the identity and influence the behavior of organizational members. Through a qualitative approach using library research methods, this study highlights how Islamic values ​​such as trustworthiness, sincerity, justice, and brotherhood are internalized in the structures, policies, and daily practices of educational institutions. Organizational culture theories such as the models of Edgar Schein and Geert Hofstede, as well as structural-functional, symbolic interactionism, and institutional approaches are used as an analytical framework. The results of the study indicate that a strong organizational culture aligned with the Islamic vision can increase organizational effectiveness, strengthen communication, and facilitate ethical and inclusive decision-making. However, challenges such as internal resistance, limited resources, and a mismatch between symbols and practices remain obstacles in the process of cultural transformation. Therefore, strategies for strengthening culture through exemplary leadership, value training, cultural symbolization, and regular evaluation are key to building an adaptive and sustainable organizational culture. This research provides theoretical and practical contributions to the development of value-based Islamic educational management